TA’LIM MUASSASASI FAOLIYATINING TASHKILIY VA IQTISODIY XUSUSIYATLARI: ZAMONAVIY BOSHQARUV VA STRATEGIK RIVOJLANISH OMILLARI (World Conference on Social Sciences, Law and Public Policy, 2026)
This article provides a deep scientific and theoretical analysis of the organizational and economic characteristics of educational institutions in the context of modern educational transformation and the digital economy. The study highlights the management model of educational institutions, economic stability, financial resource management mechanisms, strategic development factors, and the importance of innovative management technologies. It also substantiates the economic nature of educational services, their role in the development of human capital, and mechanisms for increasing the competitiveness of educational institutions.
Keywords: educational institution, educational economics, strategic management, financial resources, economic efficiency, digital transformation, innovative management, human capital, quality of education.